Electroluminescence of zinc oxide thin-films prepared via polymeric precursor and via sol-gel methods - Lima, S. A. M. [UNESP]; Cremona, M.; Davolos, Marian Rosaly [UNESP]; Legnani, C.; Quirino, W. G. (Elsevier B.V., 2007)
Zinc oxide (ZnO) is an electroluminescent (EL) material that can emit light in different regions of electromagnetic spectrum when electrically excited. Since ZnO is chemically stable, inexpensive and environmentally friendly material, its EL property can be useful to construct solid-state lamps for illumination or as UV emitter. We present here two wet chemical methods to prepare ZnO thin-films: the Pechini method and the sol-gel method, with both methods resulting in crystalline and transparent films with transmittance > 85% at 550 nm. These films were used to make thin-film electroluminescent devices (TFELD) using two different insulator layers: lithium fluoride (LiF) or silica (SiO2). All the devices exhibit at least two wide emission bands in the visible range centered at 420 nm and at 380 nm attributed to the electronic defects in the ZnO optical band gap. Besides these two bands, the device using SiO2 and ZnO film obtained via sol-gel exhibits an additional band in the UV range centered at 350 nm which can be attributed to excitonic emission. These emission bands of ZnO can transfer their energy when a proper dopant is present. For the devices produced the voltage-current characteristics were measured in a specific range of applied voltage. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: TFELD; electroluminescence; ZnO; chemical route; solid-state lightning